Leaving home to learn: Exploring Acehnese students’ awareness of language development abroad - Nur Akmaliyah; Ika Kana Trisnawati; Asma; Sri Kartika Abdul Rahman (Early Publishing Group, 2026)
Studying abroad programs are often linked to positive outcomes; however, less is known about how students from underrepresented regions interpret their progress across different dimensions of language use. This study aims to explore Acehnese students’ perceived language development during study abroad. Using a qualitative approach, seven Acehnese students in diverse international contexts were recruited through convenience sampling. Data were collected by means of semi-structured interviews and later analyzed by using thematic analysis. Six key themes emerged: confidence and agency, immersion-driven development, self-directed learning, interaction-based growth, uneven progress, and academic literacy development beyond linguistic proficiency. The findings show that language development is non-linear and shaped by access to meaningful interaction, levels of social engagement, and the ability to navigate academic and sociocultural contexts. The experiences of the student signify that development is not only about language form, but is also about academic literacy practices and identity negotiation in English-medium contexts. This study provides another perspective on study abroad outcomes, which puts emphasis on the situated and complex nature of language development among multilingual learners from peripheral contexts. Implications of this study are the need for pre-departure preparation that goes beyond language training to incorporate strategies for social integration, self-directed learning, and academic literacy. Institutions in Aceh, in particular, should also provide ongoing support to enhance students’ engagement in academic and social practices abroad.